2018
DOI: 10.1186/s41239-018-0096-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficient, helpful, or distracting? A literature review of media multitasking in relation to academic performance

Abstract: Media multitasking, using two or more medias concurrently, prevails among adolescents and emerging adults. The inherent mental habits of media multitasking-dividing attention, switching attention, and maintaining multiple trains of thought-have significant implications and consequences for students' academic performance. The goal of this review is to synthesize research on the impacts of media multitasking on academic performance. The research indicates that media multitasking interferes with attention and wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
115
3
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(132 citation statements)
references
References 55 publications
4
115
3
10
Order By: Relevance
“…The smartphone can introduce substantial burdens on a learner's cognitive resources. As it is currently conceived, the smartphone is distracting and particularly detrimental to learners attempting to study (Aharony & Zion, 2019;May & Elder, 2018). The core functionality and use of the smartphone is based largely on the notification.…”
Section: Smartphone Use and Cognitive Resourcesmentioning
confidence: 99%
“…The smartphone can introduce substantial burdens on a learner's cognitive resources. As it is currently conceived, the smartphone is distracting and particularly detrimental to learners attempting to study (Aharony & Zion, 2019;May & Elder, 2018). The core functionality and use of the smartphone is based largely on the notification.…”
Section: Smartphone Use and Cognitive Resourcesmentioning
confidence: 99%
“…In recent years, there has been mounting research interest in determining whether digital multitasking is associated with deficits or benefits to various measures of cognitive performance and information processing capacity (Alzahabi & Becker, 2013;Cain et al, 2016;Lui & Wong, 2012;Minear et al, 2013;Ralph et al, 2015;Uncapher et al, 2016). It has been broadly shown that multitasking, compared to carrying out tasks sequentially, can decrease sustained attention, impede self-regulatory abilities, and disrupt learning (Wei et al, 2012;Grieco-Calub et al, 2017;Lee et al, 2012;May & Elder, 2018;Rosen et al, 2013;Stothart et al, 2015;Wood et al, 2012).…”
Section: Digital Multitasking In Academic Settings and Cognitive Implmentioning
confidence: 99%
“…Additionally, there lacks strong support of any effects occurring beyond the negative consequences of general distraction and task-switching costs (which are not technology-specific). It should also be noted that many of the findings in support of detrimental effects of multitasking are usually achieved either in highly controlled experimental settings or focus on very narrow measures of cognitive performance (May & Elder, 2018). There may well be longer-term or higher-order benefits (or costs) to media multitasking beyond what is tested in experimental settings.…”
mentioning
confidence: 99%
“…The students' interaction was supportive, and arguments were well-structured. Furthermore, roles kept the discussion on task and there was no confusion about the responsibilities (Bruyckere et al, 2015;May and Elder, 2018;Pedro et al, 2018).…”
Section: Case 1: Social Networking Systems For Supporting Equal Partimentioning
confidence: 99%
“…For instance, technology can affect the selfdisclosure and identity management of individuals (Yee and Bailenson, 2007) as well as provide an arena for bullying (Santiago and Siklander, in review), thus running the risk of inhibiting productive social interactions or providing less than optimal support for them. In terms of group interactions and technologically enhanced collaborations in particular, challenges may relate to a cognitive load too excessive to efficiently handle content and task related activities simultaneously with social and technological factors (Bruyckere et al, 2015;May and Elder, 2018;Pedro et al, 2018) or the lack of available important social cues for social information processing, particularly in text-based communications (Kreijns et al, 2003;Walther, 2011;Terry and Cain, 2016). This discussion of technology's challenges is particularly relevant in bigger online learning communities and social networking systems, but also in small group collaboration (Bodemer and Dehler, 2011;Davis, 2016), such as in the context of games for learning, digital fabrication, and "maker" education.…”
Section: Introductionmentioning
confidence: 99%